The approach to the question about time in Being and Time. Methodic and content aspects, according to the title, the epigraph and the introduction - Carrillo Castillo, Lucy (Estudios de Filosofía, 1999)
This paper aims at showing how Heidegger poses the question about time and space in Being and Time, and how this question is the core topic of his work. After analizing, from a phenomenological view, the relation between being and time -after which the work gets its name- it is studied the quotation from The Sophist, by Plato, taken as an epigraph to Being and Time. So it is shown the aporía underlying the question: what is the subject of that work: being or time? A careful analysis of this introduction will prove there is no place for a question about being, beyond temporal boundaries and that the sense of the concept of temporality is the result of its development all through the work and not o f its fragmentry character.